Caregiver and service provider vaccine confidence following the Changchun Changsheng vaccine incident in China: A cross-sectional mixed methods study. Issue 44 (14th October 2020) - Tu, Shiyi; Sun, Fiona Yueqian; Chantler, Tracey; Zhang, Xuan; Jit, Mark; Han, Kaiyi; Rodewald, Lance; Du, Fanxing; Yu, Hongjie; Hou, Zhiyuan; Larson, Heidi
Highlights: Around 85% caregivers and 94% providers agreed vaccines were safe and effective. An immediate decline in vaccine confidence were reported after vaccine incident. Vaccine confidence regained following government and public health responses. Providers overwhelmed by workload and psychological pressure after vaccine incident. Abstract: Introduction: The Changchun Changsheng Vaccine Incident (CCVI) occurred mid-2018 and involved irregularities in the manufacture and quality control of diphtheria-tetanus-acellular-pertussis and rabies vaccines. This study investigates vaccine confidence amongst Chinese caregivers and vaccination-service providers (VSPs) six months after the CCVI. Methods: Quantitative surveys were conducted in January 2019 with 2124 caregivers of children and 555 VSPs in three areas in China. The proportions of respondents who agreed to the four statements from the Vaccine Confidence Index™ were used to measure vaccine confidence. Descriptive and univariate analyses were performed to study the level of vaccine confidence. Semi-structured interviews were conducted with 48 caregivers, 43 VSPs and 9 immunization program managers. Interviews were analyzed thematically using a combination of deductive and inductive coding. Media surveillance was conducted to monitor public responses to the CCVI. Results: Media surveillance indicated that public attention to vaccine-related issues increased sharply immediately post-CCVI but declined rapidly thereafter. Six months post-CCVI, 96.0% of caregivers and the same proportion of VSPs reported that vaccination was important and compatible with their religious beliefs. 82.7% and 88.2% of caregivers agreed that vaccines were safe and effective. 92.8% and 94.6% of VSPs agreed that vaccines were safe and effective. Both caregivers and VSPs reported an immediate decline in vaccine confidence post-CCVI. In most cases this trust was regained over time following government and public health responses, however some people remained hesitant about vaccinating their children. Many VSPs were overwhelmed by consultations, workload and psychological pressure after the CCVI. Conclusion: After an initial decline, vaccine confidence recovered to pre-incident levels six months after the CCVI. However, some caregivers moved from the higher to the lower end of the vaccine confidence spectrum, pointing to the need to promote the acceptance of vaccination especially given the need for new vaccines to control the coronavirus epidemic.